Quality of life of women from families of martyred individuals in the Kurdistan region of Iraq as a conflict area in the Middle East - Hamdia Mirkhan Ahmed (BMC, 2020)
Abstract Background Quality of life (QOL) research develops data and insight into issues that pertain not only to the individual, but that can also apply to the population as a whole. This study aimed to analyze the QOL of Kurdish women from families of martyred individuals in the Kurdistan region of Iraq. Methods A cross-sectional study of 380 women from families of martyred individuals was conducted. All women were patients at the Medical Center of Martyr Families in Erbil City from January 2018 to April 2019. Data were collected through interviews and the WHOQOL-BREF scale was used to measure QOL. The women's QOL scores were divided into four categories (i.e., quartiles): 1st, 2nd, 3rd and 4th quartile. Kruskal-Wallis and Chi-Square tests were used for data Analysis. Results The women's QOL scores fell into the following quartiles: Overall QOL and General Health (n = 66.6%) in the 1st quartile, Physical and Psychological Health (n = 56.9%) in the 2nd quartile, Social Relationships (n = 47.9%) in the 3rd quartile, Environmental health (n = 85.6%) in the 2nd and 3rd quartile. The total QOL of more than half (n = 52.1%) of the women studied were in 1st and 2nd quartiles. Conclusion Women from families of martyred individuals were not satisfied with their QOL, especially in terms of Physical and Psychological Domains. International political and humanitarian actions are needed to reduce the destructive consequences of war and conflict on these suffering women.